ANALYSIS OF TRANSITIVE AND INTRANSITIVE VERBS IN THE LANI LANGUAGE AT TIGIKUN VILLAGE, TOLIKARA REGENCY - Lemurah Wenda; Piter Mabel; Amelia Kaisepo (PT. Jurnal Center Indonesia Publisher, 2025)
Language is a system of sound symbols used by humans to interact in social life. Language has sentence elements, which consist of “Subject, Predicate, Object, and Complement”. The objectives of the study consisted of two parts. 1) to record transitive and intransitive verb sentences in the Lani Language of Tolikara Regency, 2) to describe the form of transitive and intransitive verb sentence structures in the Lani Language of Tolikara Regency. The method used in this study is descriptive. Descriptive research is conducted to describe the level of analysis, namely, analyzing and presenting facts systematically, so that they can be better understood and concluded. The researcher used an informant, the Chief of the Tribe